Zeolitic agglomerated material, preparation process, and use for non-cryogenic gas separation

JP2025032168APending Publication Date: 2025-03-11ARKEMA FRANCE SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024207082
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-21
Filing Date
2024-11-28
Publication Date
2025-03-11

Smart Images

  • Figure 2025032168000003
    Figure 2025032168000003
  • Figure 2025032168000001
    Figure 2025032168000001
  • Figure 2025032168000002
    Figure 2025032168000002
Patent Text Reader

Abstract

To provide an adsorbent material for purification of hydrogen or preparation of high-purity oxygen from air.SOLUTION: A zeolitic agglomerated material in the form of zeolite agglomerate particles comprising at least one zeolite and at least one binder is provided. A ratio of the volume-average diameter of the zeolite agglomerate particles relative to the number-average diameter of the zeolite crystals is less than or equal to 70. The volume-average diameter of the zeolite agglomerate particles is between 20 μm and 400 μm (limits included), preferably between 50 μm and 380 μm (limits included).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to specific adsorbents for the non-cryogenic separation of gases, more particularly for the non-cryogenic separation of industrial gases, and even more particularly for the separation of nitrogen by adsorption in gas streams such as air, and for the purification of hydrogen or the preparation of high purity oxygen from air by adsorption of carbon monoxide (CO) and / or nitrogen (N2). [Background technology]

[0002] The separation of nitrogen from gas mixtures is the basis of several non-cryogenic industrial processes, including the production of oxygen from air by the processes PSA (Pressure Swing Adsorption) or VPSA (Vacuum Pressure Swing Adsorption), the PSA process being one of the most important.

[0003] In this application, air is compressed and sent to a column of adsorbent with a pronounced selectivity for nitrogen molecules. Thus, oxygen, typically with a purity between 85% and 95%, and argon are produced during the adsorption cycle. After a certain time, the column is depressurized and then maintained at a low pressure, during which the nitrogen is desorbed. Repressurization is then ensured by a portion of the produced oxygen and / or air, and the cycle continues. The advantage of this method over the cryogenic method is the increased simplicity of the plant, which makes maintenance easier.

[0004] Adsorbent usage remains an essential step towards an efficient and competitive process. Adsorbent performance is linked to many factors, some of which are worth mentioning include the nitrogen adsorption capacity, the selectivity between nitrogen and oxygen, which determines the column selection and the optimization of the production yield (ratio between produced and introduced oxygen) and the adsorption kinetics, which makes it possible to optimize the cycle time and increase the productivity of the plant.

[0005] The use of molecular sieves as selective nitrogen adsorbents is well known in the art today. A class of zeolites with pore sizes of at least 0.4 nm (4 Å) is shown, for example, in US 3,140,931 for the separation of mixtures of oxygen and nitrogen. The comparative performance of the various ionic forms of zeolites, more particularly the lithium form, is described in US 3,140,933, and is presented as being the most effective in terms of selectivity.

[0006] Patent application FR 2766476 describes an improved zeolite adsorbent for separating gases in air and a method for its manufacture. The document describes an adsorbent based on LSX zeolite, containing lithium and optionally potassium, and having a zeolitic binder. This adsorbent has a diameter of 26 cm. 3 .g -1 The material is produced starting from at least 95% LSX zeolite (Si / Al atomic ratio=1) exchanged with lithium. However, it is found that the mechanical strength of these agglomerates may prove insufficient for certain applications.

[0007] Document WO2014 / 176002 describes a method for producing a zeolite adsorbent that can be used to separate gaseous compounds such as oxygen and nitrogen. The beads of the zeolite adsorbent typically have a size of 1.8 mm.

[0008] Patent application US20130340612 describes the preparation and use of adsorbent powders such as zeolites mixed with binders to form zeolite agglomerates in the form of beads. The goal of this document is to optimize the porosity profile to optimize separation efficiency. For this purpose, it is indicated in paragraph

[0063] that the bead diameter / crystal diameter ratio should be between 100 and 1000 for an approximately uniform porous structure and good mechanical strength.

[0009] The current importance of non-cryogenic processes for separating industrial gases using zeolitic adsorbents (also called "molecular sieves") means that the discovery and development of increasingly high performance adsorbents is a major objective for both gas producing companies and the companies that supply the molecular sieves. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] U.S. Pat. No. 3,140,931 [Patent Document 2] French Patent Invention No. 2766476 [Patent Document 3] International Publication No. 2014 / 176002 [Patent Document 4] US Patent Application Publication No. 2013 / 0340612 Summary of the Invention [Problem to be solved by the invention]

[0011] One of the objectives of the present invention is therefore to provide a zeolitic adsorbent with improved adsorption capacity compared to existing zeolitic adsorbents, e.g. LiLSX type, for the separation of industrial gases, in particular nitrogen and oxygen, more particularly to obtain high purity oxygen gas for medical use.

[0012] Another object is to further improve the efficiency of medical oxygen concentrators, in particular to reduce the size of the concentrators, for example by reducing the size of the adsorbent bed ("bed size"). To improve the efficiency of such concentrators, one solution is to reduce the size of the zeolitic agglomerated material, for example constituting the adsorbent bed present in said concentrators.

[0013] It has now been found that the above objects are achieved in whole or at least in part by the present invention. Other and further objects will become apparent from the following description of the invention. [Means for solving the problem]

[0014] The present invention thus proposes (V) a new high-capacity zeolitic adsorbent from crystals of LSX zeolite containing lithium for the non-cryogenic separation of industrial gases by PSA, more particularly for the separation of nitrogen and oxygen (N2 / O2), very particularly for the preparation of medical oxygen from air, and for the industrial preparation of oxygen by PSA.

[0015] Thus, according to a first aspect, the subject of the present invention is a zeolitic agglomerated material in the form of zeolitic agglomerated particles comprising at least one zeolite and at least one binder, the zeolitic agglomerated material having a ratio of the volume-average diameter of the zeolitic agglomerate particles to the number-average diameter of the zeolite crystals of less than or equal to 70, the volume-average diameter of the zeolitic agglomerated particles being between 20 μm and 400 μm, preferably between 50 μm and 380 μm, the limits being included. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The ratio of the volume-average diameter of the zeolite agglomerate particles to the number-average diameter of the zeolite crystals is generally advantageously greater than 1, preferably greater than 2 and even more preferably greater than 4. According to one preferred embodiment, this ratio is between 70 and 4, more preferably between 70 and 5.

[0017] According to one preferred embodiment, the zeolitic agglomerated material according to the invention comprises at least FAU type zeolite crystals and has a Si / Al atomic ratio, measured by X-ray fluorescence with a measurement uncertainty of ±0.05, between 1 and 2.5, preferably between 1 and 2.0, more preferably between 1 and 1.8 and most preferably between 1 and 1.6.

[0018] According to one preferred embodiment, the zeolitic agglomerated material according to the invention comprises FAU type zeolite crystals having an Si / Al atomic ratio between 1.00 and 1.50, preferably between 1.00 and 1.40, more preferably between 1.00 and 1.15, including limits.

[0019] Advantageously, the zeolitic agglomerated material according to the invention comprises crystals of FAU type zeolite, more particularly of LSX type or "low-silica X type zeolite", that is to say a zeolite with an Si / Al atomic ratio equal to 1.00±0.05. These zeolitic crystals are well known to those skilled in the art and can be prepared according to any known means, for example by reproducing and / or adapting the procedures described in application FR 2 925 478.

[0020] According to yet another preferred embodiment, the zeolitic agglomerated material of the invention has a lithium content, expressed as a weight of LiO, between 8.0% and 12.0% by weight (both limits inclusive), preferably between 9.0% and 12.0% by weight (both limits inclusive), more preferably between 10% and 12.0% by weight (both limits inclusive), relative to the total weight of the zeolitic agglomerated material.

[0021] According to one embodiment, the zeolite crystals used in the zeolitic agglomerated material of the present invention have a number-average diameter (d) between 5.0 μm and 20.0 μm, preferably between 5.0 μm and 15.0 μm. 50 ).

[0022] The average diameter of the crystals can be adjusted in particular according to the operating conditions of the synthesis and, for example, by adjusting one or more of the following parameters: the composition of the synthesis medium, the shear rate applied to the synthesis medium, the addition of less or more seeds to the synthesis medium, the temperature of the synthesis medium, the duration of the synthesis, etc.

[0023] In an advantageous embodiment of the invention, the zeolite material has a non-zeolitic phase (NZP) such that 0 < NZP ≤ 25 wt%, preferably 0 < NZP ≤ 20 wt%, more preferably 0 < NZP ≤ 15 wt%, advantageously 0 < NZP ≤ 10 wt%, and even more advantageously 0 < NZP ≤ 8 wt%, as measured by X-ray diffraction (XRD) relative to the total weight of the zeolitic agglomerated material.

[0024] In one embodiment, the zeolitic agglomerated material that can be used in the present invention has an amount of non-zeolitic phase NZP such that 0 < NZP ≤ 7 wt%, more preferably 0.5 wt% ≤ NZP ≤ 5 wt%, as measured by XRD relative to the total weight of the zeolitic agglomerated material.

[0025] The zeolitic agglomerated material according to the invention is in the form of solid particles having a size, expressed as volume-average diameter, of at most between 20 μm and 400 μm, most preferably between 50 μm and 380 μm (including both limit values).

[0026] The zeolitic agglomerated material can be obtained according to any agglomeration and shaping method known to those skilled in the art, for example, a method of shaping by stirring and collision, such as a granulator drum, for example, a continuously operating granulator plate, or a granulator mixer (also called a "nodulator") generally operated in batch mode, or a method of shaping by spraying and drying, for example, obtained in a limited way by a spray dryer, etc. These various shaping processes make it possible to achieve the desired shape and size. It should be understood that an additional sieving process may optionally be carried out to further refine the target size following these processes.

[0027] The zeolitic agglomerated material of the present invention also generally has a value between 0.50 kg·m -3 ~0.80 kg·m -3 and preferably between 0.55 kg·m -3 ~0.75 kg·m -3between 0.50 and 0.60 kg.m -3 ~0.70kg.m -3 The bulk density is between 0.01 and 0.1.

[0028] The zeolitic agglomerated materials of the invention are also characterized by very good mechanical strength, in particular a very good bulk crushing strength (BCS), measured according to the ASTM 7084-04 standard, most often greater than 1.5 MPa, generally greater than 2.0 MPa and preferably greater than 2.5 MPa.

[0029] In the most particularly preferred embodiments of the present invention, the zeolitic agglomerated material has one, two or more, or all, of the features of the above-mentioned embodiments. The total volume of macropores and mesopores of the zeolitic agglomerated materials that may be used in connection with the present invention, measured by mercury intrusion, is advantageously less than 0.15 cm 3 .g -1 ~0.5cm 3 .g -1 Between the 3 .g -1 ~0.40cm 3 .g -1 Between, very preferably 0.20 cm 3 .g -1 ~0.35cm 3 .g -1 and the measurements are carried out on agglomerated material that is at least 95% exchanged with lithium ions.

[0030] When the zeolitic agglomerated material of the invention contains several different types of zeolites, these different types of zeolites are determined by XRD. The amount of each type of zeolite is also determined by XRD and expressed as a weight percentage relative to the total weight of the adsorbent.

[0031] Consequently, in the present invention, the term "non-zeolitic phase" (or "NZP") means any phase present in the zeolitic agglomerated material other than the zeolite(s) defined above, called "zeolitic phase" or "ZP". The amount of non-zeolitic phase is expressed as the amount added to the zeolitic phase of the agglomerated material to make the total 100%, in other words: %NZP=100-%ZP, Here, %NZP represents the weight percentage of NZP and %ZP represents the weight percentage of zeolitic phase (ZP) relative to the total weight of the zeolitic agglomerated material. According to a highly preferred embodiment, the zeolitic agglomerated material of the present invention is, for example, - a material in the form of beads having a volume-average diameter of 400 μm, containing zeolite of the LSX type having a number-average diameter equal to 5 μm, corresponding to a ratio of the volume-average diameter of the particles of the adsorbent to the number-average diameter of the zeolite crystals equal to 80, or - a material in the form of beads having a volume-average diameter of 350 μm, containing zeolite of the LSX type having a number-average diameter equal to 5 μm, corresponding to a ratio of the volume-average diameter of the particles of the adsorbent to the number-average diameter of the zeolite crystals equal to 70, or - a material in the form of beads having a volume-average diameter of 250 μm, containing zeolite of the LSX type having a number-average diameter equal to 10 μm, corresponding to a ratio of the volume-average diameter of the particles of the adsorbent to the number-average diameter of the zeolite crystals equal to 25, or - a material in the form of beads having a volume-average diameter of 300 μm, containing zeolite of the LSX type having a number-average diameter equal to 6 μm, corresponding to a ratio of the volume-average diameter of the particles of the adsorbent to the number-average diameter of the zeolite crystals equal to 50, or - a material in the form of beads having a volume-average diameter of 150 μm, containing zeolite of the LSX type having a number-average diameter equal to 9 μm, corresponding to a ratio of the volume-average diameter of the particles of the adsorbent to the number-average diameter of the zeolite crystals equal to 17, or - a material in the form of beads having a volume-average diameter of 350 μm, containing LSX type zeolite with a number-average diameter equal to 11 μm, corresponding to a ratio of the volume-average diameter of the particles of the adsorbent to the number-average diameter of the zeolite crystals equal to 32, This list is not limited.

[0032] The present invention also relates to a process for the preparation of a zeolitic agglomerated material according to the invention, comprising the following steps: a) agglomeration of zeolite crystals with an agglomeration binder, preferably containing at least 80% by weight of clay(s), shaping, drying and calcination, b) optionally zeolitizing at least a portion of the binder; c) a cation exchange step; d) an optional drying step, and e) Activation step of the obtained zeolitic agglomerated material.

[0033] In the above preparation methods, all indicated amounts are calcined equivalents, i.e. expressed by weight or weight percentage, less the loss on ignition (LOI) measured for each component introduced. It is also possible to use in step a) zeolite crystals at least partially exchanged with rare earths, as described, for example, in patent US5464467.

[0034] The agglomeration step is a technique well known at present and is carried out here, for example, by agglomeration of zeolite crystals with an agglomeration binder, preferably a zeolitizable clay and / or a non-zeolitizable clay. The shaping in step a) is carried out according to techniques well known to the person skilled in the art.

[0035] As indicated above, the agglomeration binder used in step a) can be of any type known to those skilled in the art and preferably contains at least 80% by weight of clay(s) relative to the total weight of the agglomeration binder. According to one embodiment of the invention, said clay can comprise at least one zeolitizable clay, i.e. a clay that can be converted into a zeolite by any means known to those skilled in the art, for example by caustic digestion.

[0036] The term "zeolitizable clay(s)" refers to a clay or mixture of clays which can be converted into a zeolitic material by the action of an alkaline base solution, by techniques currently well known to those skilled in the art.

[0037] Clays that can be used as agglomeration binders typically belong to the family of clays: kaolinite, halloysite, nacrite, dickite, kaolin and / or metakaolin, to which a source of silica can also be added.

[0038] It is also possible to incorporate one or more other types of non-zeolitizable clays, such as, but not limited to, clays selected from attapulgite, sepiolite, bentonite, montmorillonite, and others.

[0039] Furthermore, during the agglomeration step a), it is possible to incorporate one or more organic additives with the aim of facilitating the shaping and / or imparting certain properties to the agglomerated material, such as mechanical stability, porosity profile, etc. These additives are well known to those skilled in the art and can be incorporated in amounts ranging from 0 to 5% by weight relative to the total weight of said product obtained at the end of step a).

[0040] The drying operation of step a) is carried out in the usual manner, preferably at a temperature generally between 50 and 200°C, for example at about 120°C. The calcination of step a) is also carried out according to known methods and is intended to reduce the water content and to give mechanical strength to the agglomerates by burning off the agglomeration binder. This method is generally carried out by calcination at temperatures above 200°C, typically between 250°C and 700°C, preferably between 300°C and 650°C, generally under an oxidizing and / or inert gas flush with gases such as oxygen, nitrogen, air, dried and / or decarbonated air, and oxygen-depleted air, which is optionally dried and / or decarbonated. This calcination is carried out for several hours, for example between 2 and 6 hours.

[0041] The optional zeolitization step may be carried out by immersing the agglomerates in an alkaline, generally aqueous, basic solution, for example an aqueous solution of sodium hydroxide and / or potassium hydroxide, the concentration of which is preferably greater than 0.5 M. Said concentration is generally less than 5 M, preferably less than 4 M and advantageously less than 3 M. The zeolitization is preferably carried out at elevated temperatures (higher than ambient temperature), typically around 80° C. to 100° C., in order to increase the speed of the process and reduce the immersion time to less than 8 hours. However, it would not be outside the scope of the invention to operate at lower temperatures and with longer immersion times. It would also not be outside the scope of the invention to add a solid or liquid silica source, for example sodium silicate or dissolved silica, to the basic alkaline solution during this zeolitization step.

[0042] The zeolitization step b) results in the conversion of at least a portion of the zeolitizable clay(s) contained in the binder into zeolitic material. Zeolitization is found to make it possible in particular to strengthen the mechanical strength of the weakly agglomerated zeolitic adsorbent.

[0043] This procedure makes it easy to achieve a zeolitization of at least 50% by weight, preferably at least 70% by weight, more preferably at least 80% by weight, more preferably at least 85% by weight of the zeolitizable clay(s) contained in the binder, as shown above. The next step is washing with water, followed by drying.

[0044] The cation exchange carried out in step c) consists in replacing all, or at least the majority, of the cations present on the exchangeable sites of the product obtained in step b) by lithium ions.

[0045] The term "exchangeable sites" means all exchangeable sites of the zeolite crystal(s) and those formed by any zeolitization of the binder, so that the lithium content (expressed as lithium oxide LiO) is preferably comprised between 8% and 12% by weight relative to the total weight of the zeolitic agglomerated material of the invention.

[0046] The techniques that can be used to carry out this cation exchange are again well known to the person skilled in the art and are described, for example, in patent EP 0 893 157 and can, for example, consist in contacting the product obtained in step b) with an aqueous solution of a lithium salt, advantageously lithium chloride, for example by immersion and optional stirring, at a temperature between about 10° C. and 90° C., preferably between 20° C. and 80° C. This operation can be repeated one or more times, optionally with aqueous solutions of lithium salts of different concentrations, to achieve the desired degree of exchange, which corresponds, as expressed previously, to the amount of lithium expressed as the amount of Li2O present in the zeolitic agglomerated material.

[0047] In addition to the exchange with lithium cations, it is also possible to carry out exchange with one or more other cations from groups IA, IA, IIIA and IIIB (first, second, thirteenth and third columns, respectively) of the periodic table of the elements, but also with one or more other trivalent ions from the lanthanide or rare earth series, zinc(II), copper(II), chromium(II), iron(II), ammonium and / or hydronium ions.

[0048] The drying operation is carried out in the usual manner, preferably at a temperature generally between 50 and 200°C, for example about 120°C.

[0049] The activation is also carried out according to known methods and is intended to fix the water content and the loss on ignition of the zeolitic agglomerated material within optimal limits. This treatment is generally carried out by thermal activation under oxidizing and / or inert gas flushing, in particular with gases such as oxygen, nitrogen, air, dried and / or decarbonated air, oxygen-depleted air, optionally dried and / or decarbonated, at temperatures above 200° C., typically between 250° C. and 700° C., preferably between 300° C. and 650° C. This thermal activation is carried out for several hours, for example between 2 and 6 hours.

[0050] The zeolitic agglomerated material according to the invention can be used in many applications, in particular very advantageously in the separation of industrial gases and also in the separation of gases from air, in particular for the production of high purity medical oxygen, most particularly in pressure swing processes such as, for example, the industrial N2 / O2VPSA, industrial N2 / O2PSA, medical N2 / O2VPSA and medical N2 / O2PSA processes.

[0051] The zeolitic agglomerated material according to the invention has a viscosity of 20 Ncm, measured at 25° C. and 1 bar. 3 .g -1 More than 22Ncm 3 .g -1 More preferably, 24 Ncm 3 .g -1More than 25Ncm 3 .g -1 More preferably, 26 Ncm 3 .g -1 More than 27 Ncm 3 .g -1 Most often, they have a mass adsorption capacity for nitrogen (N2) of greater than 10 ...

[0052] The adsorption process using the zeolitic agglomerated material according to the invention is usually a PSA, VSA or VPSA process, preferably a PSA or VPSA process, for N2 / O2 separation in industrial gases and N2 / O2 separation in plants producing medical oxygen.

[0053] The zeolitic agglomerated material according to the invention therefore finds a particularly advantageous application as an adsorbent element in a respiratory assisted oxygen concentrator.According to one particularly advantageous embodiment of the invention, the zeolitic agglomerated material according to the invention constitutes the active substance of a consumable cartridge of zeolitic adsorbent, which cartridge can be inserted into a respiratory assisted oxygen concentrator, which concentrator is alternatively transportable, mobile and preferably portable.

[0054] Said consumable cartridge of zeolitic sorbent, comprising at least one zeolitic sorbent as defined above, is also part of the present invention. This cartridge may have a form suitable for easy insertion and replacement in an assisted breathing oxygen concentrator. According to one embodiment, said cartridge may be produced starting from the zeolitic agglomerated material according to the present invention in the form of beads agglomerated to each other by at least one resin, preferably a polymeric resin selected from thermoplastic homopolymers and / or copolymers and polycondensates.

[0055] Non-limiting examples of such polymeric resins are polyolefins, especially low and / or high and / or very high density polyethylene, polypropylene, ethylene copolymers, ethylene-vinyl acetate copolymers, polyacrylic acid, acrylonitrile homopolymers and / or copolymers, polyacrylates, polymethacrylates, acrylate copolymers and / or methacrylate copolymers, polystyrene and / or styrene copolymers, polyesters such as polyethylene terephthalate, polybutylene terephthalate, halogenated polymers and copolymers such as poly(vinylidene difluoride) (PVDF) polymers, poly(tetrafluoroethylene) (PTFE) polymers and / or copolymers, polyamides such as polyamide-11 and polyamide-12, as well as other even and odd numbered polyamides, aromatic polyamides, polyvinyl chloride, polyurethanes, polyethersulfones, polyetherketones, polycarbonates, epoxy resins, phenolic resins, thermosetting resins and elastomeric resins, and the like, as well as mixtures of two or more thereof in any proportion.

[0056] Alternatively, the consumable cartridge may contain a fixed bed of zeolitic agglomerated material according to the invention in addition to or instead of the zeolitic agglomerated material.

[0057] According to yet another aspect, the present invention relates to an oxygen concentrator for respiratory support, which is transportable, mobile and preferably portable, and which comprises at least one zeolitic agglomerated material of the type described above, or at least one fixed adsorption bed, or at least one composite material, or at least one cartridge.

[0058] It has been observed that the zeolitic agglomerated materials according to the invention have better volumetric efficiency than currently available adsorbents, this increase in volumetric efficiency provides many advantages, one of the main ones being that it allows for a reduction in the size of equipment, particularly oxygen concentrators for respiratory support.

[0059] <Analysis method> The physical properties of the zeolitic agglomerated materials according to the invention are evaluated by methods known to those skilled in the art, the main ones of which are described below.

[0060] The number-average diameter of the zeolite crystals used in the preparation of the zeolitic agglomerated material of the present invention is estimated by observation under a scanning electron microscope (SEM).

[0061] To estimate the size of the zeolite crystals in a sample, a set of images is taken at a magnification of at least 5000x. Then, using dedicated software such as the Smile View software published by LoGraMi, the diameter of at least 200 crystals is measured, with an accuracy of around 3%.

[0062] The size recorded for each crystal is the size of the largest cross section of the crystal in question. Particles smaller than 0.5 μm in size that may be present in the zeolite agglomerates are not taken into account in the count.

[0063] The resulting particle size distribution is equivalent to the average of the particle size distributions observed for each image. Peak widths and number-average diameters are calculated by conventional methods known to those skilled in the art, applying the statistical rules of the Gaussian distribution.

[0064] The elemental chemical analysis of the zeolitic agglomerated materials according to the invention can be carried out according to various analytical techniques known to those skilled in the art, including, for example, the technique of chemical analysis by X-ray fluorescence as described in the standard NF EN ISO 12677:2011 on a wavelength dispersive spectrometer (WDXRF) from Bruker Tiger S8.

[0065] X-ray fluorescence is a non-destructive spectral technique that utilizes the photoluminescence of atoms in the X-ray range to establish the elemental composition of a sample. Excitation of the atoms, typically by an X-ray beam or electron bombardment, produces specific radiation after the atoms return to their ground state. Measurement uncertainties of less than 0.4% by weight are traditionally obtained for each oxide after calibration.

[0066] Other analytical methods are described, for example, by atomic absorption spectrometry (AAS) and inductively coupled plasma atomic emission spectrometry (ICP-AES), as described in NF EN ISO 21587-3 or NF EN ISO 21079-3 on a machine of the type Perkin Elmer 4300DV.

[0067] X-ray fluorescence spectroscopy has the advantage that it is almost independent of the chemical combination of the elements, allowing accurate quantitative and qualitative determination. After calibration for the individual oxides SiO2 and Al2O3, and also for various oxides (e.g. those derived from exchangeable cations such as sodium), measurement uncertainties of less than 0.4% by weight have traditionally been obtained. The ICP-AES method is particularly suitable for the determination of the lithium content, which allows the calculation of the lithium oxide content.

[0068] Thus, the above elemental chemical analysis makes it possible to verify both the Si / Al ratio of the zeolite used in the zeolitic agglomerated material and the Si / Al ratio of the zeolitic agglomerated material. In the present description, the measurement uncertainty for the Si / Al ratio is ±5%. The measurement of the Si / Al ratio of the zeolite present in the agglomerated material can also be carried out by solid-state silicon nuclear magnetic resonance (NMR) spectroscopy.

[0069] The quality of ion exchange is related to the number of moles of the cation in question in the zeolitic agglomerated material after exchange. More specifically, the degree of exchange by a given cation is estimated by evaluating the ratio of the number of moles of said cation to the total number of moles of exchangeable cations. The respective amount of each cation is evaluated by chemical analysis of the corresponding cation. For example, the degree of exchange by sodium ions is estimated by the ratio of the number of moles of Na + The total number of cations and the total number of exchangeable cations (e.g., Ca 2+ , K + , Li + , B.A. 2+ , Cs + , Na +etc.), the amount of each of the cations being evaluated by chemical analysis of the corresponding oxide (Na2O, CaO, KO, BaO, Li2O, Cs2O, etc.). This calculation method also takes into account possible oxides present in the residual binder of the zeolitic agglomerated material.

[0070] The bulk crush strength of the zeolitic adsorbents according to the present invention is characterized according to the ASTM 7084-04 standard.

[0071] The bulk density of the zeolitic agglomerated material according to the invention is measured as described in the DIN 8948 / 7.6 standard.

[0072] The purity of the zeolite in the zeolitic adsorbent of the present invention is assessed by X-ray diffraction analysis, known to those skilled in the art by the acronym XRD, this characterization being carried out on a Bruker XRD machine.

[0073] This analysis makes it possible to identify the various zeolites present in the agglomerated material, since each zeolite has a unique diffractogram defined by the positions of the diffraction peaks and their relative intensities.

[0074] The zeolitic adsorbent was crushed, then spread and smoothed on the sample carrier by simple mechanical compression. The conditions for obtaining the diffractogram, generated on a Bruker D8 Advance machine, were as follows: Cu tube for use at 40kV-30mA, Soller slit size = 2.5°, irradiation surface width 16mm, A sample device rotating at 10 rpm, Measurement range: 4°<2θ<70°, Increment: 0.015°, Measurement time per increment: 0.8 seconds.

[0075] The interpretation of the obtained diffractograms is performed with the EVA software, which uses the ICDD PDF-2 Release 2011 database for the identification of zeolites.

[0076] The amount of FAU zeolite fraction by weight is determined by XRD analysis. This method is also used to determine the amount of non-FAU zeolite fractions. The analysis is performed on a Bruker machine and the amount of zeolite fraction by weight is then evaluated using Bruker's TOPAS software.

[0077] The gravimetric adsorption capacity of a zeolitic adsorbent at 25°C and 1 bar is determined from the measurement of its adsorption isotherm at 25°C for a gas such as nitrogen or oxygen.

[0078] Prior to adsorption, the zeolitic agglomerated material was heated at 300-450°C in vacuum (6.7.10 -4 The mixture is degassed under a pressure of less than 0.001 Pa for 9 to 16 hours. The adsorption isotherms are then measured on a Micromeritics ASAP 2020 machine, taking at least 10 measurement points at relative pressure ratios P / P0 between 0.001 and 1.

[0079] The mass adsorption capacity of the zeolitic agglomerated material is read on an isotherm at 25 °C under a pressure of 1 bar and is given in Ncm 3 .g -1 It is expressed as:

[0080] The volumetric adsorption capacity of the zeolitic agglomerated material at 25° C. and 1 bar is calculated from the mass adsorption capacity by multiplying the mass adsorption capacity by the bulk density of the zeolitic agglomerated material, the bulk density being measured as described in the DIN 8948 / 7.6 standard. The mean volume diameter (or "volume-mean diameter") of the zeolitic agglomerated material of the present invention is determined by analysis of the particle size distribution of a sample of the adsorbent material by imaging according to the ISO 13322-2:2006 standard, using a conveyor belt that allows the sample to pass in front of a camera lens.

[0081] The volume-mean diameter is then calculated from the particle size distribution applying the ISO 9276-2:2001 standard. In this specification, the term "volume-mean diameter" or "size" is used for the zeolitic adsorbent. The accuracy is as low as 0.01 mm for the size range of the zeolitic adsorbent material of the present invention. [Brief description of the drawings]

[0082] [Figure 1] The manufactured assembly is described. EXAMPLES

[0083] The invention will now be described with the aid of the following examples, the purpose of which is to illustrate certain embodiments of the invention, but not to limit the scope of the invention as claimed in the claims.

[0084] [Example 1 (Comparative): d 50 Preparation of zeolitic agglomerated materials with LSX zeolite crystals of 1.3 μm In the following text the masses given are expressed as calcined equivalents.

[0085] As described in FR 2925478, 50 A homogeneous mixture consisting of 1700 g of LSX zeolite crystals with a diameter of 1.3 μm, 300 g of kaolinite from Charente, and an amount of water such that the loss on ignition of the preformed paste was 39% was subjected to shear at a rate of 135 s -1 The paste thus prepared is used to manufacture beads of zeolitic agglomerated material.

[0086] The beads obtained are selected by sieving in order to recover beads having a diameter between 0.3 mm and 0.8 mm and a volume-average diameter equal to 0.50 mm.

[0087] The beads are dried overnight in a ventilated oven at 80°C. Afterwards, the beads are calcined at 550°C for 2 hours under a blanket of decarbonated dry air. After cooling, 100 g of these (agglomerated) beads are mixed with 100 g.l of water at a temperature controlled at 98°C. -1 The agglomerates are then immersed in 750 ml of an aqueous solution of sodium hydroxide at a concentration of 1000 g / l. The system is kept at temperature with gentle stirring for 3 hours. The agglomerates are then washed with water until the final pH of the wash water is close to 10.

[0088] Next, 20 ml.g. -1 Five successive exchanges are carried out with 1M lithium chloride solution at a solids ratio of 20 ml.g. Each exchange lasts 4 hours at 100°C, with intermediate washes that allow to remove excess salt at each step. In the final step, 20 ml.g. -1 The beads are washed four times at ambient temperature with 0.01% ethanol and 0.01% ethanol. The beads are dried overnight in a ventilated oven at 80° C. The beads are then activated at 550° C. for 2 hours under a blanket of decarbonated dry air.

[0089] The lithium oxide Li2O content, determined by ICP-AES, is 10.6% by weight relative to the total weight of the zeolitic agglomerated material. The median diameter of the beads remains unchanged at 0.50 mm. The bulk mechanical crush strength of the lithium-exchanged LSX zeolite beads is 1.4 MPa and the bulk density is 0.58 kg.m -3 , the Si / Al ratio of the zeolitic material is equal to 1.02 and the NZP is equal to 3%.

[0090] The mass adsorption capacity at 1 bar and 25°C is 24.7 Ncm 3 .g -1 The ratio of bead volume-average diameter / LSX crystal number-average diameter is 385.

[0091] [Example 2 (Comparative): d 50 Preparation of zeolitic agglomerated material with LSX crystallites of 5.6 μm d 50LSX zeolite crystals having a diameter of 5.6 μm are prepared as described in Comparative Example 1 above, but at a shear rate of 5 s -1 d 50 A homogeneous mixture is prepared consisting of 1700 g of these LSX zeolite crystals, 0.0001 μm, 300 g of kaolinite from the Charentais, 40 g (calcined equivalent) of colloidal silica sold under the name Klebosol® 30, and a quantity of water such that the loss on ignition of the paste before molding is 39%.

[0092] The zeolitic agglomerated material is then prepared according to the protocol described in Comparative Example 1 above.

[0093] The lithium oxide Li2O content, determined by ICP-AES, is 10.7% by weight relative to the total weight of the zeolitic agglomerated material. The volume-average diameter of the beads is 0.50 mm. The mechanical bulk crushing strength (BCS) of the lithium-exchanged LSX zeolite beads is 2.6 MPa and the bulk density is 0.63 kg.m -3 , the Si / Al ratio of the zeolitic material is equal to 1.03 and the NZP is equal to 2.7%.

[0094] The mass adsorption capacity at 1 bar and 25°C is 27 Ncm 3 .g -1 The ratio of bead volume-average diameter / LSX crystal number-average diameter is 90.

[0095] [Example 3 (Invention): d 50 Preparation of a zeolitic agglomerated material with LSX crystallites of 5.6 μm and a ratio of bead diameter / LSX crystallite diameter of 62. d 50 = 5.6 μm LSX zeolite crystals are prepared as described in Comparative Example 2 above. 50 A homogeneous mixture is prepared consisting of 1700 g of LSX zeolite crystals, =5.6 μm, 300 g of Zeoclay® attapulgite and an amount of water such that the loss on ignition of the paste before molding is 39%.

[0096] The paste thus prepared is used to manufacture beads of zeolitic agglomerated material.

[0097] The beads obtained are selected by sieving in order to recover beads having a diameter between 0.10 mm and 0.50 mm and a volume-average diameter equal to 0.35 mm.

[0098] The beads are dried overnight in a ventilated oven at 80° C. The beads are then calcined at 550° C. for 2 hours under a blanket of decarbonated dry air.

[0099] Next, 20 ml.g. -1 The lithium cation exchange is carried out by five successive exchanges with 1M lithium chloride solution at a solids ratio of 20 ml.g. Each exchange lasts 4 hours at 100°C, with intermediate washes, which allow to remove excess salt at each step. In the final step, 20 ml.g. -1 Wash four times at ambient temperature.

[0100] The beads are dried overnight in a ventilated oven at 80° C. The beads are then activated at 550° C. for 2 hours under a blanket of decarbonated dry air.

[0101] The lithium oxide Li2O content, determined by ICP-AES, is 8.9% by weight relative to the total weight of the zeolitic agglomerated material. The volume-average diameter of the beads is 0.35 mm. The mechanical bulk crushing strength (BCS) of the lithium-exchanged LSX zeolite beads is 2.1 MPa and the bulk density is 0.63 kg.m -3 , the Si / Al ratio of the zeolitic material is equal to 1.25 and the NZP is equal to 17%.

[0102] The mass adsorption capacity at 1 bar and 25°C is 21 Ncm 3 .g -1 The ratio of bead volume-average diameter / LSX crystal number-average diameter is 62.

[0103] [Example 4 (Invention): d50 Preparation of a zeolitic agglomerated material with LSX crystals of 7 μm and a ratio of bead diameter / LSX crystal diameter of 43. d 50 LSX zeolite crystals of diameter 7 μm are prepared as described in Comparative Example 1 above, but at a shear rate of 2.5 s -1 d 50 A homogeneous mixture is prepared consisting of 1700 g of LSX zeolite crystals, 0.001 μm, 300 g of Zeoclay® attapulgite and an amount of water such that the loss on ignition of the paste before molding is 39%. The paste thus prepared is used to manufacture beads of zeolitic agglomerated material.

[0104] The beads obtained are selected by sieving in order to recover beads having a diameter between 0.10 mm and 0.50 mm and a volume-average diameter equal to 0.30 mm.

[0105] The beads are dried overnight in a ventilated oven at 80° C. The beads are then calcined at 550° C. for 2 hours under a blanket of decarbonated dry air.

[0106] Next, 20 ml.g. -1 The lithium cation exchange is carried out by five successive exchanges with 1M lithium chloride solution at a solids ratio of 20 ml.g. Each exchange lasts 4 hours at 100°C, with intermediate washes, which allow to remove excess salt at each step. In the final step, 20 ml.g. -1 Wash four times at ambient temperature.

[0107] The beads are dried overnight in a ventilated oven at 80° C. The beads are then activated at 550° C. for 2 hours under a blanket of decarbonated dry air.

[0108] The lithium oxide Li2O content, determined by ICP-AES, is 9.2% by weight relative to the total weight of the zeolitic agglomerated material. The volume-average diameter of the beads is 0.30 mm. The mechanical bulk crushing strength (BCS) of the lithium-exchanged LSX zeolite beads is 2.1 MPa and the bulk density is 0.63 kg.m -3 , the Si / Al ratio of the zeolitic material is equal to 1.25 and the NZP is equal to 17%.

[0109] The mass adsorption capacity at 1 bar and 25°C is 22 Ncm 3 .g -1 The ratio of bead volume-average diameter / LSX crystal number-average diameter is 43.

[0110] [Example 5 (Invention): d 50 Preparation of a zeolitic agglomerated material with LSX crystals of =6.5 μm and a ratio of bead diameter / LSX crystal diameter =38. d 50 LSX zeolite crystals having a diameter of 6.5 μm are prepared as described in Comparative Example 1 above, but at a shear rate of 3 s -1 d 50 A homogeneous mixture is prepared consisting of 1700 g of LSX zeolite crystals having a diameter of 6.5 μm, 300 g of kaolinite from the Charentais, 40 g (calcined equivalent) of colloidal silica sold under the name Klebosol® 30, and a quantity of water such that the loss on ignition of the paste before molding is 39%.

[0111] The zeolitic agglomerated material is then prepared according to the protocol described in Comparative Example 1 above.

[0112] The lithium oxide Li2O content, determined by ICP-AES, is 10.2% by weight relative to the total weight of the zeolitic agglomerated material. The volume-average diameter of the beads is 0.25 mm. The mechanical bulk crushing strength (BCS) of the beads of lithium-exchanged LSX zeolite is 2.2 MPa and the bulk density is 0.65 kg.m -3, the Si / Al ratio of the zeolitic material is equal to 1.05 and the NZP is equal to 2.8%.

[0113] The mass adsorption capacity at 1 bar and 25°C is 26 Ncm 3 .g -1 The ratio of bead volume-average diameter / LSX crystal number-average diameter is 38.

[0114] Example 6: Determination of column height to obtain 95% pure oxygen N2 / O2 separation tests were carried out on two fixed beds of adsorbent using pressure swing adsorption (PSA). Figure 1 describes the assembly produced. Two columns (1) and (2) filled with zeolitic agglomerated material (14), with an internal diameter equal to 6 cm and with equal internal height, are fed with dry air (13) and intermittently depressurized by valves (4) and (5). Different sets of columns of different heights are provided. Table 1 shows the respective states of the valves according to the adsorption and desorption phases.

[0115] [Table 1]

[0116] Dry air is fed to the column (1 or 2) and the stream (13) passes through the column and, consequently, through the zeolitic agglomerating material (14), which preferably adsorbs nitrogen, so that the oxygen-enriched air leaves the column via valve (7 or 8) and then passes through the non-return valve (9 or 10) towards the buffer tank (11). The regulating valve (6) regulates the flow rate of the column at 5 NL.min -1 Gas is continuously delivered at the outlet (16) at a constant flow rate fixed at .

[0117] When the column (1 or 2) is not being fed, it is depressurized by opening valve (4 or 5) to atmosphere (15), which corresponds to the "closed valve" mode, thereby allowing the nitrogen to desorb. The adsorption and desorption phases alternate. The duration of these phases is fixed per cycle and they are adjustable.

[0118] Valve 12 is a purge valve. Valve 12 is permanently open to allow desorption of some of the oxygen and nitrogen produced in the adsorption column. The time during which stream (13) is fed to column (1 or 2) is called the adsorption time.

[0119] The tests are performed successively with alternating adsorption and desorption phases, the duration of each phase (adsorption / desorption) cycle ranging from 0.5 to 15 seconds, this duration being adapted to the size of the column.

[0120] The column is dimensioned to obtain an outlet oxygen concentration of 95%. The oxygen concentration at the outlet (16) is measured by a Servomex 570A oxygen analyzer. The test results are shown in the table below.

[0121] [Table 2]

Claims

1. A zeolitic agglomerated material in the form of zeolite agglomerate particles comprising at least one zeolite and at least one binder, the ratio of the volume-average diameter of the zeolite agglomerate particles to the number-average diameter of the zeolite crystals being less than or equal to 70, the volume-average diameter of the zeolite agglomerate particles being between 20 μm and 400 μm, inclusive, preferably between 50 μm and 380 μm, inclusive.

2. 2. The zeolitic agglomerated material according to claim 1, comprising at least FAU type zeolite crystals and having a Si / Al atomic ratio between 1 and 2.5, preferably between 1 and 2.0, more preferably between 1 and 1.8, most preferably between 1 and 1.6, measured by X-ray fluorescence with a measurement uncertainty of ±0.

05.

3. Li 2 3. Zeolitic agglomerated material according to claim 1 or 2, in which the lithium content, expressed by the weight of O, is between 8.0% and 12.0% by weight (inclusive), preferably between 9.0% and 12.0% (inclusive) and more preferably between 10% and 12.0% by weight (inclusive), relative to the total weight of the zeolitic agglomerated material.

4. The zeolite crystals have a number-average diameter (d 50 The material according to any one of claims 1 to 3, having a molecular weight of 1.0 or more.

5. 5. The material according to any one of claims 1 to 4, wherein the amount of non-zeolitic phases (NZP) is such that 0<NZP≦25 wt.-%, preferably 0<NZP≦20 wt.-%, more preferably 0<NZP≦15 wt.-%, advantageously 0<NZP≦10 wt.-%, and even more advantageously 0<NZP≦8 wt.-%, relative to the total weight of the zeolitic agglomerated material, as measured by X-ray diffraction (XRD).

6. Bulk density is 0.50 kg.m -3 ~0.80kg.m -3 between 0.55 kg.m -3 ~0.75kg.m -3 More preferably between 0.60 kg.m -3 ~0.70kg.m -3 The material according to any one of claims 1 to 5, wherein

7. Steps below a) agglomeration of zeolite crystals with an agglomeration binder, preferably containing at least 80% by weight of clay, shaping, drying and calcining; b) optionally zeolitizing at least a portion of the binder; c) a cation exchange step; d) an optional drying step, and e) Activation step of the obtained zeolitic agglomerated material A method for preparing the zeolitic adsorbent of any one of claims 1 to 6, comprising:

8. 8. The method according to claim 7, wherein the optional zeolitization step can be carried out by immersing the agglomerates in an alkaline basic solution, generally aqueous, for example an aqueous solution of sodium hydroxide and / or potassium hydroxide, the concentration of which is more preferably greater than 0.5 M.

9. Separation of industrial gases and also gases from air, in particular for the production of high purity medical oxygen and most particularly in pressure swing processes, e.g. industrial N 2 / O 2 VPSA, industrial N 2 / O 2 PSA, Medical N 2 / O 2 VPSA and Medical N 2 / O 2 Use of a material according to any one of claims 1 to 6 as a nitrogen adsorbent in a PSA process.

10. 10. The use according to claim 9 as an adsorption element in an oxygen concentrator for respiratory assistance.

11. A consumable zeolitic adsorbent cartridge comprising at least one zeolitic adsorbent material according to any one of claims 1 to 6.

12. 12. The cartridge of claim 11, further comprising at least one resin, preferably a polymeric resin, preferably a polymeric resin selected from thermoplastic homopolymers and / or copolymers and polycondensates.

13. A transportable, mobile, preferably portable oxygen concentrator for respiratory assistance comprising at least one zeolitic adsorbent material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Bounded zeolitic adsorbent, method for its production and its use for the non cryogenic separation of process gases

    FR2766476A1

  • High Rate Compositions

    US20130340612A1

  • Separation of an oxygen-nitrogen mixture

    US3140931A

  • Zeolitic adsorbents for use in adsorptive separation processes and methods for manufacturing the same

    WO2014176002A1